Dialogues on literacy and literacy in the universe of Early Childhood Education - Persicheto, Aline Juliana Oja; Argenti, Marcia Cristina [UNESP] (Univ Nove Julho, 2023)
Discussions on the teaching of reading and writing in the context of Early Childhood Education reveal different positions, indicating diversified practices that vary according to the theoretical concepts that underlie the pedagogical work in this school phase. This article presents part of a post-doctoral theoretical research developed between 2020 and 2022 that aimed to analyze the legal and scientific path of the process of consolidation of Early Childhood Education as part of Basic Education, in the last decade, as well as the construction of its identity as a systematized learning space, directed to the formation and development of the child, with emphasis on Literacy, Literacy and Ludicity practices. The main objective of the article is to discuss the concepts of literacy and literacy and the possibilities of exploring such processes in the universe of Early Childhood Education, through a pedagogical work that values play as the main activity of childhood.
Keywords: literacy; child education; pedagogical practices